Regards d’acteurs et d’actrices scolaires quant à l’engagement en faveur d’une culture d’équité dans des écoles secondaires québécoises - Corina Borri-Anadon; Geneviève Audet; Eve Lemaire (Recherches en Éducation)
This paper presents the results of a research project into the intercultural climate in schools and on the academic success of immigrant students in Québec. The intercultural climate in eight secondary public schools is documented from the standpoint of various school and community stakeholders, students, and parents. More specifically, the paper focuses on the commitment to promoting cultural equity, which is identified through interviews with the targeted stakeholders on exclusionary practices and processes and the practices implemented to counter them. The results identify five areas of vulnerability among certain minoritized groups of students: the transition from welcoming to regular classes for those students learning French, evaluation and support for those experiencing learning or behavioral difficulties, the referral of these students to adult education programs or work-oriented training programs, their participation in extracurricular activities and their access to special school projects. Nonetheless some schools do report the introduction of many equity practices in response to the exclusionary ones. However, these initiatives are mostly occasional, voluntary, and pertain to interactions between individuals. These findings call for a discussion on the importance of systemic and concerted initiatives towards achieving equity.